The Refutation of Gorgias: Notes on a Contradiction - Güremen, Refik (Peitho. Examina Antiqua, 2017)
This paper claims that Socrates’ refutation of Gorgias in the eponymous dialogue is designed not to find out the truth about the nature of the art of rhetoric itself but to refute the master of rhetoric himself. I try to justify this claim by displaying some major contradictions between the conclusions reached at with Gorgias and those reached at with Polus. When these contradictions are taken into account, the discussion with Polus is to be seen as reflecting the genuine Socratic position about rhetoric, whereas the discussion with Gorgias seems only to be devised as a dexterity in refutation.